THE USE OF CIVILIZATION VI IN HISTORY TEACHING: DIGITAL GAMES AS A DIDACTIC TOOL (REMUNOM, 2025)
This study analyzes the use of the video game Civilization VI as a didactic tool in History education. Digital games with historical content enable the experimentation of the past through simulations, going beyond mere entertainment and providing resources for the construction of historical knowledge in the classroom. The research reflects on the role of these games in teaching, presenting the Civilization franchise as an example of historical representation and detailing the features of Civilization VI as a simulator of the past. The methodology adopted is qualitative and exploratory, including the analysis of the game and a review of academic studies published between 2016 and 2025, primarily retrieved from Google Scholar using the descriptors “Sid Meier’s Civilization VI” and “Civilization VI and History Education.” The study shows that Civilization VI contributes to making lessons more dynamic, engaging, and immersive, integrating historical theory and practice. The results reinforce the relevance of digital games as pedagogical tools capable of promoting meaningful learning and stimulating critical reflection on the past.